Distinctive encodings and the production effect: failure to retrieve distinctive encodings decreases recollection of silent items. Issue 2 (7th February 2020) - Ozubko, Jason D.; Bamburoski, Luke D.; Carlin, Kayla; Fawcett, Jonathan M.
ABSTRACT: Studies have shown that when aloud and silent items are studied together, silent items are remembered more poorly than when they are studied independently. We hypothesise that this cost to silent items emerges because, at test, participants search for memories of having said items aloud and when those memory searches fail, participants become uncertain about whether silent items were studied. This effect should be exaggerated if other unique distinctive encoding conditions are also included at study (e.g., mumbling, writing, typing, etc.). To test this prediction, we examined the impact of introducing mumbled, "important" (i.e., words that participants are told are the most important to remember), and mouthed words to a study list of aloud and silent words. Introducing mumbled and "important" words further impaired the recollection of silent items. Introducing mouthed items did not further impair the memorability of silent items because mouthing and speaking aloud are so similar and hence, are not fully unique from each other. The memorability of aloud items was unaffected in all conditions. These results suggest that participants search for distinctive encoding information at test, and only for items that fail those searches (i.e., silent items) do they lose confidence.